Detection of the Gear Pair with Crack Defects Based on Double-tree Complex Wavelet - Wang Tianyang; Tao Xueheng; Dai Peng; Ran Haifeng (Jixie chuandong)
Cylindrical spur gear pair is a commonly used key transmission part in the modern machinery industry. Root cracks often occur due to the periodic load and fatigue wear of the tooth surface. As a result, the vibration and noise of the gear pair are increased, which seriously affect the working performance of the mechanical system and need to be detected in time. However, there are factors such as random vibration and white noise in the working environment of the gear pair, so that the noise is generated in the vibration spectrum of the gear pair, and the defect frequency is submerged, which is not conducive to the identification of the crack defect of the gear pair. For the vibration signal of the gear pair with crack defects, wavelet transform is used to decompose and reconstruct the signal, and the noise reduction model based on double-tree complex wavelet is established to realize the effective noise reduction of the vibration signal and form a gear pair crack defect detection method. The experiment results show the noise reduction effect of this method is better than the commonly used hard threshold function wavelet noise reduction and the soft threshold function wavelet noise reduction algorithms, the defect type of the gear piar can be judged more accurately using this method and it provides a scientific basis for judging the state of the cylindrical spur gear pair.